Analysis of Environmental, Social and Governance (ESG) Performance in Mineral and Coal Mining Companies - Fajar Kurniawan; Juniati Gunawan (International Journal of Technology and Education Research, 2024)
This study aims to analyse Environmental, Social and Governance (ESG) performance, which includes: 1) analysing the performance of ESG implementation through disclosures in the sustainability report, 2) analysing challenges in ESG implementation, and 3) analysing strategies in facing challenges in ESG implementation. This research uses qualitative methods in analysing ESG performance through disclosures based on the International Council on Mining & Metal (ICMM) Principles framework, challenges faced in implementing and improving ESG performance, and strategies applied to improve ESG performance. The subjects of this study are coal mining companies (PT A and PT B) and mineral mining companies (PT C and PT D), which were selected by purposive sampling, taking into account the largest capitalisation in the mineral mining and coal mining sub-sector companies, which are listed on the Indonesia Stock Exchange (IDX), and represent mineral and coal mining companies, both private and state-owned. The results showed that in the disclosure of the performance of the ICMM principles in the sustainability report from 2018 to 2022, it is known that the highest disclosure is the performance indicator on Principle 5 - Occupational Health and Safety (75%) and the lowest performance indicator on Principle 3 - Human Rights (30%). The challenges in ESG implementation are the lack of adoption of several international standards and guidelines for corporate social management. This study also found that the presence of top management support, the existence of clear policies and roadmaps for ESG implementation, a clear organisational structure, and the preparation of competent human resources are strategies to improve ESG performance.